The nutritional value of grain sorghum - V. V. Kovtunov; N. A. Kovtunova; O. A. Lushpina; N. N. Sukhenko; N. G. Ignatieva (Зерновое хозяйство России, 2018)
He nutritional value of grain sorghum Grain sorghum is an ecologically adaptive, heat and drought resistant culture. Sorghum grain is good concentrated forage for domestic animals and poultry which has a positive effect on their growing and development and produces high yields and good quality of husbandry products. The purpose of the work is to determine the content of exchangeable energy and fodder units in sorghum kernels in the process of feeding of different animals and birds. The objects of the study were 307 collection samples and varieties of grain sorghum developed by FSBSI ARRIGC named after I.G. Kalinenko, namely ‘Khazine 28’, ‘Zernogradskoe 53’, ‘Luchistoe’, ‘Orlovskoe’, ‘Velikan’, ‘Zernogradskoe 88’. The conducted study has showed that sorghum grain with 189 f.u. (min=187 f.u., max=193 f.u.) is the most nutritional one for poultry. Grain with 176-181 f.u. (average=178 f.u.) per 100 kg is the best for pig raising and grain with 124 f.u. is the best for cattle breeding. The forage produced from sorghum grain possessed the least nutrition in feeding sheep (120 f.u. (min=118 f.u., max=123 f.u.)). According to the study, it has been established that 100kg of sorghum grain contain 1491-1523 mJ (average=1507 mJ) of exchangeable energy in feeding poultry; 1457-1484 mJ (average=1472 mJ) in feeding pigs; 1282-1309 mJ (average=1295 mJ) in feeding sheep and 1264-1286 mJ (average=1276 mJ) in feeding cattle. Among the grain sorghum varieties developed in ARRIGC named after I.G. Kalinenko and approved to use, the white kernelled varieties ‘Velikan’ and ‘Zernogradskoe 88’ possess the largest nutritional value. The content of fodder units and exchangeable energy of these varieties is 123-193 f.u. and 1291-1529 mJ in dependence of the kinds of domestic animals.